Community Response, Preparedness and Disaster Risk-Reduction A Case Study of Manipur Floods 2015 - Zutshi, Bupinder; Verma, Rakesh Kumar (European Scientific Journal, ESJ, 2017)
The flood of 2015 affected entire Thoubal district and parts of Chandel district in Manipur state of India. According to the government reports, nearly 600 square kilometers of area with over 500,000 populations were affected in the Thoubal and Chandel districts. Majority of the population in the flood affected area are farmers, whose paddy crop cultivation was destroyed and it also affected crop production for the next year due to acute shortage of seeds. Fisheries farms got submerged and people lost livelihood opportunities. Animal life also suffered due to inundation of inhabited plain areas for several days. The market and shops were closed and many were submerged for at least one week. Since it was the season for agricultural plantation, the farmers also suffered from food security for the entire season. The present study examines causes and consequences that lead to the worst floods of July- August 2015 in the plains of Manipur state. The paper also examines the level of local community response towards prevention and preparedness and disaster risk-reduction. The study indicates the lack of protective and preparedness measures, while dealing with such magnitude of floods hazard.